Tripartite analysis of financial development, trade openness and economic growth: Evidence from Ghana, Nigeria and South Africa - Kizito Uyi Ehigiamusoe; Hooi Hooi Lean (Contemporary Economics, 2018)
This study examines the tripartite relationship between financial development, trade openness and economic growth in Ghana, Nigeria and South Africa for the 1980-2014 period. The study reveals a long-run causal relationship between financial development, trade openness and economic growth, thereby supporting finance- and trade-led growth hypotheses for Ghana, Nigeria and South Africa. Moreover, long-run causality from financial development and economic growth to trade openness is found for Ghana. In the short-run, there is evidence of causality from growth to financial development for Ghana, from trade openness to financial development for Nigeria and from growth and financial development to trade openness for South Africa. The findings of this study are robust to alternative proxies of financial development and various diagnostic tests. The study shows that financial development and trade openness can be deployed to accelerate growth, while growth and financial development can be used to promote trade openness. Additionally, trade openness spurs financial development. Therefore, a tripartite relationship exists between the three variables. Hence, interdependence between financial development, trade openness and economic growth is found and consequent policy recommendations are made.
Keywords: G15; F10; O11; 330; Financial development; Trade openness; Economic growth